THE CORRELATION BETWEEN STUDENTS’ MOTIVATION TO LEARN ENGLISH AND SPEAKING ACHIEVEMENT AT SMKN 1 NGASEM KEDIRI - Rikha Niswatul Auliya; Agus Edi Winarto; Ary Setya Budhi Ningrum (IKIP Siliwangi, 2022)
Motivation is crucial in the learning process. Motivation is also support and satisfaction in the serious attempt to reach the goal. The purpose of this study is to determine whether or not there is a significant relationship between students' motivation to learn to English and their speaking achievement at SMKN 1 Ngasem Kediri. The researcher selected 67 participants as a sample from a total population of 702 students. SPSS version 26.0 was used to analyse the data. The tool was a questionnaire with 26 items and one question in a speaking assessment. The researcher used descriptive statistics and Kendall's Tau calculation to analyse the data. According to the research findings, students' motivation to learn to English was classified as extremely poor (value = 0,193). The value result revealed that the probability level was 0,024. It is possible to claim that 0,024 0,05 indicated that H0 was rejected and Ha was accepted. Thus, in SMKN 1 Ngasem Kediri, there is a very low significant correlation between students' motivation to learn English and speaking achievement. As a consequence of various variables, such as a lack of sample to the population, students' potential or naturally intelligent, and many intelligence characteristics to speak English effectively, the outcome is a very low correlation. Keywords: Correlation, Learning, Motivation, Speaking, Achievement